2008
DOI: 10.1002/j.2051-3909.2008.tb00088.x
|View full text |Cite
|
Sign up to set email alerts
|

A 3D conformal radiation therapy class solution for dose escalated prostate irradiation

Abstract: Prostate cancer is a dose responsive neoplasm i.e. the higher the dose of radiation administered, the more likely it is to attain local tumour control. However, high doses without careful conformal treatment planning leads to increased complication rates. This study aims to determine the ideal dosimetric and clinically relevant 3D conformal radiation therapy (3D‐CRT) plan for 78 Gy dose escalated prostate treatment. A pilot study was performed on two patients using computed tomography (CT) images previously ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…The results of The present study are in agreement with that obtained by Vaezzadeh et al (20) if increasing beam energy, and number of fields , this will spares organs at risk and improves dose conformity index to PTV .Also Runham et al (21) concluded that the 6-field technique produced a plan with significantly smaller dose to the femoral heads when compared to the 5-field method for 3DCRT of prostate cancer treatment.…”
Section: Dose To Organs At Risk (Oar)supporting
confidence: 92%
“…The results of The present study are in agreement with that obtained by Vaezzadeh et al (20) if increasing beam energy, and number of fields , this will spares organs at risk and improves dose conformity index to PTV .Also Runham et al (21) concluded that the 6-field technique produced a plan with significantly smaller dose to the femoral heads when compared to the 5-field method for 3DCRT of prostate cancer treatment.…”
Section: Dose To Organs At Risk (Oar)supporting
confidence: 92%